Which molecular markers for assessing which taxonomic level? The case study of the mite family Phytoseiidae (Acari: Mesostigmata). (8th May 2016) - Vicente dos Santos, Victor; Tixier, Marie‐Stephane
Abstract: The use of molecular markers for resolving systematics issues has improved our knowledge of life history. However, for the taxa studied herein—the predatory mite family Phytoseiidae—molecular phylogeny is impeded by a lack of suitable markers for deeper taxonomic levels. This study aims (i) to establish DNA amplification protocols for molecular markers known to resolve supraspecific nodes in other taxa, (ii) to determine their individual performance in assessing the clustering of species, genera, tribes and subfamilies, and (iii) to characterize the additional information provided when markers are concatenated. A new phylogenetic index is proposed based on ecological concepts, considering trees as a community of nodes. New and efficient protocols for DNA amplification of six molecular markers are provided. The concatenated tree globally provides more robust and reliable information, especially for deeper nodes. However, for assessing species identification and within‐genera phylogenies, the combined use of six markers does not seem necessary, underlining the need to resize experiments depending on their taxonomic objectives. Finally, this study lays the methodological foundations with which to test the present Phytoseiidae classification as the first phylogeny obtained shows incongruence with the present morphological classification.